How Universities Have Betrayed Reason and Humanity—And What's to Be Done About It - Maxwell, Nicholas (Frontiers in Sustainability, 2021)
In 1984 the author published From Knowledge to Wisdom, a book that argued that a revolution in academia is urgently needed, so that problems of living, including global problems, are put at the heart of the enterprise, and the basic aim becomes to seek and promote wisdom, and not just acquire knowledge. Every discipline and aspect of academia needs to change, and the whole way in which academia is related to the rest of the social world. Universities devoted to the pursuit of knowledge and technological know-how betray reason and, as a result, betray humanity. As a result of becoming more intellectually rigorous, academic inquiry becomes of far greater benefit to humanity. If the revolution argued for all those years ago had been taken up and put into academic practice, we would now live in a much more hopeful world than the one that confronts us. Humanity would have begun to learn how to solve global problems; the Amazon rain forests would not face destruction; we would not be faced with mass extinction of species; and almost certainly, Brexit would not have been voted for in the UK in 2016, and Trump would not have been elected President in the USA. An account is given of work published by the author during the years 1972 to 2020 that expounds and develops the argument. The conclusion is that we urgently need to create a high-profile campaign devoted to transforming universities in the way required so that humanity may learn how to make social progress towards a better, wiser, more civilized, enlightened world.